MULTIDISCIPLINARY APPROACH TO IDENTIFICATION OF FISHERY SYSTEMS IN AMAZONIAN RESERVOIR: CASE STUDY IN TUCURUÍ DAM - Severiano Pereira BRAZ NETO; Antônio Marcos de Melo XAVIER; Claudmilson Rodrigues DE MESQUITA; Laudiceia de ABREU COSTA; Flávia ROSEIRA dos Reis; Israel Hidenburgo Aniceto CINTRA; Tommaso GIARRIZZO; Bianca BENTES (Boletim do Instituto de Pesca)
Dams cause profound changes in the structure of environments and local fishing practices. One example of these impacts is the Tucuruí dam, in the southeast of the state of Pará, in northern Brazil. The changes were gradual, but eventually established unique fishery systems and capture techniques that were consolidated over time. The present study used a rapid analysis technique based on the Métier principle to identify 14 fishing systems with distinct characteristics, although a more holistic approach (dimensions: economic, social, technological, and management), supported the identification of four clearly distinguishable groups. From the management perspective, studies of this type are important because they permit the establishment of more effective practices based on the deficiencies found in the different systems or their respective groups.